Characteristics of Neuropsychiatric Systemic Lupus Erythematous in Dr. Sardjito General Hospital - Tri Wirasto, Ronny; Winengku Basuki Adi (Jurnal Psikiatri Surabaya, 2024)
Introductions: Systemic lupus erythematosus (SLE) is one of the diseases that affects the system organs. Neuropsychiatric SLE (NPSLE) refers to the display of SLE involving both neurologic and psychiatric conditions. Methods: This retrospective study used inpatient and outpatient data from patients diagnosed with unspecified SLE and also included psychiatric manifestations between 2017 and 2021. Results: The patients' age range was from under 10 to over 70 years old, and the average age was 31.49 years old. The highest percentage was between 31 and 40 years old, which was 27%. Out of 100 patients, 61 received the majority of their care from the internist. The highest percentage of psychiatric disorders was unspecified depressive disorder, with 17%. The second-largest proportion was other specified neurotic disorders, which was 11%. Additionally, 10% of the patients experienced a mild cognitive illness. Based on gender, women had a higher proportion compared to men. Conclusions: Our study showed that there were 100 NPSLE cases over five years, and the highest percentages were depressive disorder, neurotic symptoms, and mild cognitive disorder.